The Effect of Work Motivation and Work Discipline on Employee Performance at PT. Liza Christina Garment Industry Sukabumi Regency - Muhamad Luki; Muhammad Sini (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to ascertain how employee performance at PT. Liza Christina Garment Industry Sukabumi Regency is impacted by work motivation and discipline. Descriptive and associative research methods with a quantitative approach are employed. 35 respondents from PT. Liza Christina Garment Industry Sukabumi Regency made up the sample for this study, which was carried out utilizing a total sampling approach in conjunction with the non-probability sampling technique. The validity and reliability test was the instrument utilized, followed by the classical assumption test. Multiple linear regression analysis, Pearson correlation analysis, and coefficient of determination analysis were the methods employed to ascertain the link and effect. The findings of the studies that have been done indicate that job motivation has an impact. impact employee performance of 0.588, meaning that a one-time increase in the work variable will result in a 0.588-fold rise in employee performance. The effect of partial work discipline on employee performance is 0.270; a one-time increase in the work discipline variable will result in a 0.270-fold rise in employee performance values. Together or separately, work motivation and work discipline have a 63% positive impact on employee performance, according to the computation results and coefficient of determination. The remaining 37% is influenced by the work environment, collaboration, pay, and other factors that were not examined. Based on these findings, it can be said that work motivation and work discipline, either separately or in combination, significantly impact employee performance as the dependent variable